2006
DOI: 10.1093/nar/gkj516
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hsp90 acts synergistically with topoisomerase II poisons to increase the apoptotic killing of cells due to an increase in topoisomerase II mediated DNA damage

Abstract: Topoisomerase II plays a crucial role during chromosome condensation and segregation in mitosis and meiosis and is a highly attractive target for chemotherapeutic agents. We have identified previously topoisomerase II and heat shock protein 90 (Hsp90) as part of a complex. In this paper we demonstrate that drug combinations targeting these two enzymes cause a synergistic increase in apoptosis. The objective of our study was to identify the mode of cell killing and the mechanism behind the increase in topoisome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Barker et al recently demonstrated that inhibition of heat shock protein 90 (Hsp90) with geldanamycin disrupts the Hsp90-topo II interaction leading to an increase of unbound topo II. In the presence of a topo II poison the elevated unbound topo II levels resulted in an increase in cleavable complexes and a corresponding increase in DNA damage and cell death (25). Similarly, in the present study, we demonstrate that when a topo II poison is present, increased levels of enzymatically active topo II protein results in increased DNA damage and increased cell death.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Barker et al recently demonstrated that inhibition of heat shock protein 90 (Hsp90) with geldanamycin disrupts the Hsp90-topo II interaction leading to an increase of unbound topo II. In the presence of a topo II poison the elevated unbound topo II levels resulted in an increase in cleavable complexes and a corresponding increase in DNA damage and cell death (25). Similarly, in the present study, we demonstrate that when a topo II poison is present, increased levels of enzymatically active topo II protein results in increased DNA damage and increased cell death.…”
Section: Discussionsupporting
confidence: 82%
“…Increasing the expression and activity of topoisomerase as a strategy to enhance topo II poison efficacy has been the subject of ongoing studies (25). Barker et al recently demonstrated that inhibition of heat shock protein 90 (Hsp90) with geldanamycin disrupts the Hsp90-topo II interaction leading to an increase of unbound topo II.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to suggest that the genotoxic stress induced by aberrant entry into mitosis with unrepaired DNA damage was sufficient to account for the increased cell death observed following combination ganetespib-doxorubicin exposure. Of interest, doxorubicin also functions as a topoisomerase II inhibitor and HSP90 blockade can enhance the activity of such poisons through disruption of a protective HSP90-topoisomerase II complex (40,41). Furthermore, the doxorubicin-cyclophosphamide doublet forms the basis of most systemic TNBC therapies and the addition of ganetespib to this regimen conferred superior efficacy in MDA-MB-231 xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…To determinate whether drug inhibits topo II without drug-adducted DNA [28], 2 µg of nuclear extract (4 µl) was incubated with drug for 20′ on ice, then this reaction was incubated with 50 ng kDNA (2 µl) in the presence of topo II assay buffer (1 µl). Reactions were stopped by addition of 1/5 stop buffer/gel loading dye (5% Sarkosil, 0.125% bromophenol blue, 25% glycerol) and digest with 50 µg/ml of proteinase K for 30 min at 37°C.…”
Section: Decatenation Assaymentioning
confidence: 99%